2014
DOI: 10.1002/2014jd021485
|View full text |Cite
|
Sign up to set email alerts
|

Convective transport of water vapor into the lower stratosphere observed during double-tropopause events

Abstract: We present in situ observations of convectively injected water vapor in the lower stratosphere from instruments aboard two aircraft operated during the Deep Convective Clouds and Chemistry experiment. Water vapor mixing ratios in the injected air are observed to be 60–225 ppmv at altitudes 1–2 km above the tropopause (350–370 K potential temperature), well above observed background mixing ratios of 5–10 ppmv in the lower stratosphere. Radar observations of the responsible convective systems show deep overshoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
124
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(133 citation statements)
references
References 62 publications
9
124
0
Order By: Relevance
“…Therefore, the spatial structure of young air masses characterized by enhanced values of emission tracers from India/China resembles a bubble within the upper troposphere. These air masses are transported eastwards along the subtropical jet and most likely enter the extratropical lower stratosphere driven by Rossby wave breaking events associated with double tropopauses (e.g., Vaughan and Timmis, 1998;Castanheira and Gimeno, 2011;Ungermann et al, 2013;Homeyer and Bowman, 2013;Homeyer et al, 2014). Our simulations show that after entering the lower stratosphere, these air masses are mixed irreversibly with the surrounding stratospheric air.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, the spatial structure of young air masses characterized by enhanced values of emission tracers from India/China resembles a bubble within the upper troposphere. These air masses are transported eastwards along the subtropical jet and most likely enter the extratropical lower stratosphere driven by Rossby wave breaking events associated with double tropopauses (e.g., Vaughan and Timmis, 1998;Castanheira and Gimeno, 2011;Ungermann et al, 2013;Homeyer and Bowman, 2013;Homeyer et al, 2014). Our simulations show that after entering the lower stratosphere, these air masses are mixed irreversibly with the surrounding stratospheric air.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies also found intrusions of tropospheric air into the lower stratosphere associated with extratropical double tropopauses (e.g., Pan et al, 2009;Homeyer et al, 2011;Vogel et al, 2011b;Schwartz et al, 2015;Wu and Lü, 2015). Further, it was shown that double tropopauses are frequently associated with Rossby wave breaking events along the subtropical jet (e.g., Vaughan and Timmis, 1998;Castanheira and Gimeno, 2011;Ungermann et al, 2013;Homeyer and Bowman, 2013;Homeyer et al, 2014).…”
Section: Isentropic Transport Pathways Into the Lower Stratospherementioning
confidence: 88%
See 1 more Smart Citation
“…lofting biomass-burning plumes, penetrating into the lowermost stratosphere, and generating stratospheric intrusions along the sides of storms. Additional studies show that the aircraft data, especially the DC-8 lidar data, provided unique depictions of convectiveinduced mixing between the stratosphere and troposphere, via both direct injections of water into the stratosphere (Homeyer et al 2014) and wrapping of stratospheric air around the anvil of storms (Pan et al 2014). The DC3 data are also being analyzed to characterize different anthropogenic and biogenic sources of volatile organic compounds and the tropospheric distribution of aerosol composition, including brown carbon (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This topic has attracted much recent attention with the development of satellite observations [1][2][3][4][5][6]. Penetrating mesoscale convective complexes (MCCs) are deep convective systems that have important effects on stratospheric-tropospheric exchange and the structure of the upper troposphere and lower stratosphere.…”
Section: Introductionmentioning
confidence: 99%